An Intellectual History of Political Corruption - Buchan, B. author. aut Link
VI, 291 p.
Keywords: Few concepts have witnessed a more dramatic resurgence of interest in recent years than corruption. This book provides a compelling historical and conceptual analysis of corruption which demonstrates a persistent oscillation between restrictive 'public office' and expansive 'degenerative' connotations of corruption from classical Antiquity to 1800.